Proceedings of the 13th International Conference on Geotechnical Engineering in Tropical Regions (GEOTROPIKA 2024) - Siti Norafida, Jusoh (Springer Nature, 2025)
Lecture Notes in Civil Engineering (LNCE) publishes the latest developments in Civil Engineering—quickly, informally and in top quality. Though original research reported in proceedings and post-proceedings represents the core of LNCE, edited volumes of exceptionally high quality and interest may also be considered for publication. Volumes published in LNCE embrace all aspects and subfields of, as well as new challenges in, Civil Engineering.